Subdomain separability in global optimization - Jens Deussen; Uwe Naumann (Journal of Global Optimization, 2022)
We introduce a generalization of separability for global optimization, presented in the context of a simple branch and bound method. Our results apply to continuously differentiable objective functions implemented as computer programs. A significant search space reduction can be expected to yield an acceleration of any global optimization method. We show how to utilize interval derivatives calculated by adjoint algorithmic differentiation to examine the monotonicity of the objective with respect to so called structural separators and how to verify the latter automatically.
Keywords: 510; Global optimization; Algorithmic differentiation; Branch and bound; Interval adjoints; Search space reduction; Separable functions